Thailand Economic Monitor, June 2010 - World Bank (Washington, DC, 2017)
The Thai economy runs on a single engine: external demand. The economic roller coaster since the onset of the global financial crisis can be overwhelmingly attributed to fluctuations in the output of three sectors most sensitive to external demand: manufacturing, logistics (transportation and storage), and tourism (hotels and restaurants). As global trade contracted between the fourth quarter of 2008 and first quarter of 2009, Thailand's real gross domestic product (GDP) fell 6.3 percent, before rebounding 6.9 percent through the end of 2009 on a revival in actual and expected external demand. At the end of 2009, real GDP was back to pre-crisis levels, as measured in seasonally adjusted terms. For 2009 as a whole, however, real GDP fell 2.2 percent. The dominance of sectors linked to external demand over Thailand's growth dynamics is not new. Both sets of sectors grew at about the same pace prior to the 1997 financial crisis. However, a structural break took place in the aftermath of the crisis, when sectors linked to external demand grew an average of 6.1 percent between 2001 and 2007 compared to a 4.3 percent growth rate of other sectors. While the sectors linked to external demand are expected to grow below the historical average in the near term due to lower growth in demand from advanced economies, a reversal of the structural change observed since 1998 is unlikely. This will require an acceleration of the growth of the sectors linked to domestic demand. But the constraints that limited the growth of these sectors in the past not only remain but have been compounded in the near term by the escalation of the political conflict. This will ensure that growth rates in sectors linked to domestic demand will also remain below their (already low) historical averages and the dominance of external demand on the economy will continue to increase.